Gandhi and Gulen : Comparing their views for peace building exercises - Alam, Anwar (Voices of Teachers and Teacher Educators, 2015)
Revered as ‘special person with divine grace’ among their people at popular level, both Gandhi and Gulen envision a free, peaceful, democratic, tolerant and non-violent world and have generated positive public actions to achieve this goal through legal, peaceful and non-violent means. Though the world view of both are deeply grounded in religious philosophy, Gandhi’s world view is primarily constructed through Santan Hindu religious tradition, while Gulen’s world view is primarily filtered through the prism of Sunni orthodox Islamic traditions with a focus on Turkish Islamic history. Gandhi, unlike Gulen, was not a product of religious seminary or had undergone any scholastic training. On the other hand, Gulen, unlike Gandhi, is neither a product of modern educational system nor a national- political leader of the masses -fighting for the political liberation of people. Notwithstanding the differences in the political context, time-period and religious traditions and other semantic differences between the two, both are credited to have conducted public actions on the basis of their understanding of ‘religious truth’ in pursuit of a free, peaceful, democratic, tolerant and non- violent world through legal, peaceful and non- violent means